La Iglesia Católica del Brasil : límites del aggiornamento - IreIand, Rowan (Estudios Internacionales, 1974)
Analyzing the case of the Church in Brazil, this article aims to provide a partial answer to the question regarding whether it is possible today to study the problems of the Church based on the concept of "elasticity of traditional structures" that defines Latin American societies. Until 1952 the Brazilian Church neglected the national organization: the isolated parishes communicated with each other through the diocesan Curia and the dioceses related directly to Rome and only secondarily with each other. The form and function of the Church changed very rapidly, in various aspects, during the 50-60 period. However, weighing heavily against it, when the actions of the Catholic radicals in Brazil are analyzed, and an accurate explanation is sought for their ineffectiveness, we must note the powerful political coercion against the "aggiornamento" since the military coup in 1964, which were intensified when the 5th Institutional Act was issued, in December 1968.